Impact of accreditation on Caribbean medical schools’ processes (Canadian Medical Education Journal, 2021)
Background: Caribbean graduates contribute significantly to the US healthcare workforce. The accreditation requirements of local governments vary from one Caribbean island to another island. The Educational Commission for Foreign Medical Graduates (ECFMG) requirement that all future applicants be graduates from accredited medical schools drove Caribbean medical schools to seek accreditation. Accreditation has been found to significantly impact the educational processes of Canadian medical schools. Our study aims at investigating Caribbean medical school leaders’ perceptions of the impact of accreditation on their school’s processes.Methods: This qualitative study and data analysis were done using a framework analysis. Academic leaders and faculty members from three different types of Caribbean medical schools (accredited, denied-accreditation schools, never applied for accreditation) were interviewed using semi-structured interviews.Results: A total of 12 participants from six different Caribbean medical schools participated in the interview process. Themes of processes influenced by accreditation at Caribbean medical schools were similar to those found in the Canadian context and align with best practices of Continuous Quality Improvement (CQI).Conclusions: Caribbean medical schools are changing their educational processes as a result of accreditation requirements. Some processes are not maintained in a continuous manner, raising questions about the development of a true CQI culture.